2022
DOI: 10.1146/annurev-biochem-032620-105728
|View full text |Cite
|
Sign up to set email alerts
|

The Purinosome: A Case Study for a Mammalian Metabolon

Abstract: Over the past fifteen years, we have unveiled a new mechanism by which cells achieve greater efficiency in de novo purine biosynthesis. This mechanism relies on the compartmentalization of de novo purine biosynthetic enzymes into a dynamic complex called the purinosome. In this review, we highlight our current understanding of the purinosome with emphasis on its biophysical properties and function and on the cellular mechanisms that regulate its assembly. We propose a model for functional purinosomes in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 67 publications
(137 reference statements)
2
20
0
Order By: Relevance
“…As an example, the purinosome is a biomolecular condensate of enzymes from de novo purine biosynthesis. It is formed through liquid-liquid phase separation in cultured cells and proposed to facilitate metabolite channeling (Pedley et al, 2022). We do not know the full set of functional mammalian metabolons, how they are regulated to match metabolic supply and demand, and which if any are rele-vant to disease.…”
Section: Radioactive Methods For Metabolic Imagingmentioning
confidence: 99%
“…As an example, the purinosome is a biomolecular condensate of enzymes from de novo purine biosynthesis. It is formed through liquid-liquid phase separation in cultured cells and proposed to facilitate metabolite channeling (Pedley et al, 2022). We do not know the full set of functional mammalian metabolons, how they are regulated to match metabolic supply and demand, and which if any are rele-vant to disease.…”
Section: Radioactive Methods For Metabolic Imagingmentioning
confidence: 99%
“…Although this work used in vitro human CD34 + cell cultures, the same group showed that in vivo stress erythropoiesis induced by phenylhydrazine treatment in mice was blocked by DON, while myelopoiesis increased in the spleen ( Oburoglu et al, 2014 ; Oburoglu et al, 2016 ). In cancer cells, highly efficient usage of the PPP and Ser/Gly pathways relies on the establishment of metabolons, like the purinosome, which is a complex of at least 10 enzymes that uses metabolic channeling to drive de novo purine biosynthesis ( An et al, 2008 ; Zhao et al, 2015 ; Pedley et al, 2022 ). It remains to be demonstrated whether signals that promote the proliferation of SEPs also drive the formation of the purinosome and other metabolons to increase metabolic efficiency.…”
Section: Metabolic Control Of Progenitor Proliferationmentioning
confidence: 99%
“…The most persuasive work on metabolons involves de novo purine biosynthesis, in which 5-ribosyl-1-pyrophosphate (PRPP) is converted in ten steps to inosine monophosphate (IMP) which is then used to make AMP or GMP. The ten steps are catalyzed by a six-enzyme metabolon called the purinosome, the transient assembly of which correlates with cellular purine requirement. Highlights of a recent review include the mechanism by which the metabolon is transported to its target and direct visualization of the metabolon in action …”
Section: Nanoconfinement In Biologymentioning
confidence: 99%
“…143 Seminal experiments involving fusion proteins in Arabidopsis thaliana, transient expression in Sorghum bicolor, and metabolon isolation and reconstitution in liposomes, demonstrated the dynamic nature of a metabolon for dhurrin synthesis. 144,145 The most persuasive work on metabolons involves de novo purine biosynthesis, 146 in which 5-ribosyl-1-pyrophosphate (PRPP) is converted in ten steps to inosine monophosphate (IMP) which is then used to make AMP or GMP. The ten steps are catalyzed by a six-enzyme metabolon called the purinosome, the transient assembly of which correlates with cellular purine requirement.…”
Section: Substrate Channelling In Permanentmentioning
confidence: 99%